Editorial Introduction - Miguel, Paulo A. Cauchick (Brazilian Journal of Operations & Production Management, 2010)
This special issue of the Brazilian Journal of Operations and Production Management presents some of the best papers of the ICPR Americas 2006. The third edition of the American International Conference on Production Research (ICPR) was held in Curitiba, Brazil, from July 30th thru August 2nd, 2006, and was organized by the Brazilian Association of Production Engineering (ABEPRO), and the Industrial & Systems Engineering Graduate Program (PPGEPS) of the Pontifi cal Catholic University of Paraná (PUCPR). It was an offi cial Conference of the International Foundation for Production Research (IFPR). There were about 200 papers submitted from Brazil, Argentina, Canada, Chile, Colombia, Costa Rica, England, France, Germany, Japan, Mexico, Portugal, Russia, Turkey and United States. A double-blind review process selected approximately 100 papers for oral presentations (allocated in 5 Technical sessions) and 30 papers as posters. Among them, best ones were selected and the authors were invited to submit a more robust article. Then, these papers were double-blind reviewed and some of those that achieved the higher marks were selected to be part of this issue.